2004
DOI: 10.1021/ef034095c
|View full text |Cite
|
Sign up to set email alerts
|

Bed Agglomeration Characteristics of Biomass Fuels Using Blast-Furnace Slag as Bed Material

Abstract: Agglomeration of bed material may cause severe operating problems during fluidized bed combustion. The attack or coating layers that are formed on the bed particles during combustion play an important role in the agglomeration process. To reduce bed agglomeration tendencies, alternative bed materials may be used. In this paper, bed agglomeration characteristics during the combustion of biomass fuels using a relatively new bed material (iron blast-furnace slag) as well as ordinary quartz sand were determined. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 8 publications
7
74
1
Order By: Relevance
“…Therefore, it was important to determine whether their original composition could have affected the compounds bonding to their surface during combustion. The results, however, showed no indications of differences between the particles and, in contrast to previous findings, no signs could be found of alkali silicate melt on the inner surface of the silica sand particles [6,19,20].…”
Section: Sem-edx Analysis On Ashescontrasting
confidence: 98%
“…Therefore, it was important to determine whether their original composition could have affected the compounds bonding to their surface during combustion. The results, however, showed no indications of differences between the particles and, in contrast to previous findings, no signs could be found of alkali silicate melt on the inner surface of the silica sand particles [6,19,20].…”
Section: Sem-edx Analysis On Ashescontrasting
confidence: 98%
“…For circulating fluidized bed, silicacontaining sand is usually used as the bed material, and potassium in biomass can react with silica to form a low temperature eutectic during combustion, which will damage the operation [49][50][51][52][53][54][55][56][57][58][59][60][61][62] and some possible ways have been used to solve the alkali metal related problems [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Circulating Fluidized Bed Combustionmentioning
confidence: 99%
“…The methods mentioned above can only prolong the defluidization time but still cannot avoid agglomeration and defluidization. Some previous studies have shown that biomass co-combustion with peat or coal can be an inexpensive measure for preventing bed agglomeration (Arvelakis and Frandsen, 2007;Brus et al, 2004;Gogebakan et al, 2009;Lundholm et al, 2005). The main mechanism for preventing the formation of viscous coatings is the retention of alkali by chemisorptions or physical adsorption by minerals and ash constituents in coals (Lundholm et al, 2005).…”
Section: Introductionmentioning
confidence: 99%